Analysis and Application of Supply Chain Management for Cosmetic Inventory at Hayati Store Using PHP Programming Language and MYSQL Database - Delima, Putri; Syafrika Deni Rizki; Radius Prawiro (Indonesian Journal of Economic & Management Sciences, 2024)
This research focuses on Hayati Store, a business specializing in the sale of beauty tools and beauty products. The study explores various aspects of beauty product management at Hayati Store, including demand planning, inventory management, and distribution during sales, using Supply Chain Management (SCM) methodology. Implementation will be carried out using PHP programming language and MYSQL database to facilitate effective management. Although the store has computerized cosmetic and beauty tool sales, the current system only covers sales aspects, lacking information on stock turnover from product receipt to warehouse inventory management. This research aims to optimize the distribution process during sales and transform existing data into a comprehensive Supply Chain Management system